Cultura de consumo e produção de sentidos no texto publicitário - Ribeiro, Maria Clara Maciel de Araújo; Xavier, Mariana Ramalho Procópio (Linguagens & Cidadania, 2017)
This article discloses a discussion concerning the culture of consumption from the analysis of an advertising text. We assume that the publicity almost always operates with the objective of reaffirming values and habits that tacitly moves through the society and many times with the purpose of creating new consumption habits based on those already existent. From the view of the French oriented Discourse Analysis, we aimed to identify how the meaning is produced in certain advertising announcement and the strategies used for the incitement of consumption.